2017
DOI: 10.1002/prp2.307
|View full text |Cite
|
Sign up to set email alerts
|

Medication errors involving anticoagulants: Data from the Danish patient safety database

Abstract: Reporting of adverse incidents is mandatory in Denmark. All reported adverse incidents are made anonymously, and stored in an encrypted database. It is the purpose of this descriptive study to describe the severity of adverse medication incidents caused by oral anticoagulants in hospitals. All moderate, severe and fatal reports concerning non‐vitamin K antagonist oral anticoagulants were analyzed from date of marketing until July 8 2014. The data collection for warfarin was from January 1 2014 until July 8 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 16 publications
1
20
1
Order By: Relevance
“…anticoagulant-related medication errors occurred mainly in the prescribing phase and in about 56% of errors lowmolecular-weight heparins (LMWH) were involved [2,4]. Consistently, a similar descriptive study on the Danish patient safety database reported that the adverse medication incidents occurred mainly in the prescribing phase, and in about 80% of incidents the errors occurred at the time of sector changes (at the admission, at the discharge or ward changes) [5]. Among different error subtypes occurring in the prescribing phase, the wrong dosage and drug omission have been repeatedly found as the most common subtype [3,6,7].…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…anticoagulant-related medication errors occurred mainly in the prescribing phase and in about 56% of errors lowmolecular-weight heparins (LMWH) were involved [2,4]. Consistently, a similar descriptive study on the Danish patient safety database reported that the adverse medication incidents occurred mainly in the prescribing phase, and in about 80% of incidents the errors occurred at the time of sector changes (at the admission, at the discharge or ward changes) [5]. Among different error subtypes occurring in the prescribing phase, the wrong dosage and drug omission have been repeatedly found as the most common subtype [3,6,7].…”
mentioning
confidence: 69%
“…From this population, all patients admitted to our in-patient wards, from 21.08.2017-20.08.2018, who concomitantly received at least two ACs were included in the study. Subsequently, the following patients have been excluded: [1] patients who received the anticoagulants separately, no overlapping prescription [2] patients treated with the combination of heparin/ heparin analogs and vitamin-K antagonists (VKA) [3] patients receiving heparin/ heparin analogs based on a weekly schedule such as patients with hemodialysis [4] patients receiving low-dose alteplase (= < 4 mg) as a catheter locking solution [5] patients treated with the combination of VKA and direct oral anticoagulants (DOACs) during bridging from DOACs to VKA [6] patients who explicitly refused participation in research.…”
Section: Patient Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a study conducted in Denmark with the purpose to describe the severity of adverse medication incidents caused by oral anticoagulants in hospitals showed that all fatal and almost all serious adverse medication incidents were associated with the prescribing phase of the medication process. In addition, during admission and surgery, prescribing excess anticoagulant was the most frequent problem and, on the other side, during discharge, prescribing insufficient anticoagulant was the most frequent problem . As more drugs to improve patient outcomes enter the health care system, potential new interactions become apparent.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, during admission and surgery, prescribing excess anticoagulant was the most frequent problem and, on the other side, during discharge, prescribing insufficient anticoagulant was the most frequent problem. 89 As more drugs to improve patient outcomes enter the health care system, potential new interactions become apparent. These interactions can impact on a drug's absorption, distribution, metabolism, excretion, or actual clinical effect.…”
Section: Secondary Care For Episodes Of Ill Healthmentioning
confidence: 99%